2008
DOI: 10.1128/aac.00628-08
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole Combined with Amphotericin B, an Effective Therapy for a Murine Disseminated Infection Caused by Rhizopus oryzae

Abstract: In a murine model of disseminated zygomycosis, low doses of amphotericin B (0.3 mg/kg body weight/day) combined with posaconazole (40 mg/kg/day) prolonged survival and reduced tissue burden with respect to that of controls and that of both drugs administered alone. Results were similar to those obtained with amphotericin B given alone at 0.8 mg/kg/day.Zygomycosis is an opportunistic fungal infection that causes a high degree of morbidity and mortality in immunocompromised patients, particularly those with hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 13 publications
3
67
0
1
Order By: Relevance
“…68 A few animal studies have been conducted to explore the in vivo efficacy of posaconazole in screening models of disseminated mucormycosis that used survival and/or fungal tissue burden as end points. [69][70][71][72][73] Posaconazole prolonged the survival and reduced tissue burden in neutropenic mice with disseminated Mucor infection and was as effective as standard AmB at the highest dose level. 69 In non-immunocompromised mice, no beneficial effects were observed against R. oryzae, while partial activity was shown against Lichtheimia corymbifera and dose-dependent activity against Rhizopus microsporus.…”
Section: Posaconazolementioning
confidence: 99%
“…68 A few animal studies have been conducted to explore the in vivo efficacy of posaconazole in screening models of disseminated mucormycosis that used survival and/or fungal tissue burden as end points. [69][70][71][72][73] Posaconazole prolonged the survival and reduced tissue burden in neutropenic mice with disseminated Mucor infection and was as effective as standard AmB at the highest dose level. 69 In non-immunocompromised mice, no beneficial effects were observed against R. oryzae, while partial activity was shown against Lichtheimia corymbifera and dose-dependent activity against Rhizopus microsporus.…”
Section: Posaconazolementioning
confidence: 99%
“…Livio Pagano, 1 Oliver A. Cornely, 2,3 Alessandro Busca, 4 Morena Caira, 1 Simone Cesaro, 5 Cristiana Gasbarrino, 6 Corrado Girmenia, 7 Werner J. Heinz, 8 Raoul Herbrecht, 9 Cornelia Lass-Flörl, 10 Annamaria Nosari, 11 Leonardo Potenza, 12 Zdenek Racil, 13 1-2011-2012).…”
Section: Letters To the Editormentioning
confidence: 99%
“…6,7 However, pre-clinical studies in neutropenic and diabetic ketoacidotic mice with IM reported no improvement in survival under a combination of posaconazole and liposomal amphotericin B (LAmB), compared to L-AmB monotherapy. 8,9 Given the rarity of IM, these results have not been evaluated systematically in a clinical setting. Therefore, the value of combining a lipid formulation of AmB (Lip-AmB) with posaconazole for the treatment of IM remains a subject of controversy and discussion.…”
mentioning
confidence: 99%
“…Both studies found that addition of posaconazole to polyenes resulted in no additive benefit compared with polyene therapy alone (42,43). No clinical studies have evaluated combination posaconazole-polyene therapy for mucormycosis.…”
Section: Combination Antifungal Therapymentioning
confidence: 99%